SOPISTIKASI TEORI KONFLIK PEKERJAAN-KELUARGA: SEBUAH KAJIAN KRITIS - I Gusti Ayu Manuati Dewi (PIRAMIDA, 2012)
This paper provides extensive review and categorization of the work-family conflict (WFC) literature. Review is begun with existence of six theoretical frameworks which most widely utilized in role conflict literature: role-related theory, resource-related theory, spillover theory, scarcity hypothesis, institutional theory, and social identity theory. The review is completed by recommendation of study and theory extension in the future by their shopistication from culture-neutral study and theory to culture-sensitive study and theory. This extension is expected to beneficial for both developing three ways interaction study and theory of role conflict and giving additional knowledge for organization and management in arranging role-balance initiative programs.